Effects of no-take marine reserves on fish assemblages in Brazil: an assessment using stereo-videos - Rolim, Fernanda Andreoli [UNESP] (2019)
The establishment of no-take marine reserves (NTRs), i.e. areas with total fishing restrictions, has been an alternative worldwide aiming to preserve both biodiversity and ecosystem functions. Brazil has important NTRs with few studies describing their relevance and efficiency for marine life. With this, the central objective of this thesis was to evaluate the effects of NTRs on fish assemblage, testing the hypothesis that the differences in richness, abundance, biomass and fish body size is more explained by protection status than environmental characteristics. Thus, innovative techniques in Brazil, Baited Remote Underwater stereo-Videos (stereo-BRUVs) and Diver Operated stereo-Videos (stereo-DOVs) were tested in the Southwestern Atlantic, comparing with traditional visual census (stationary point count and belt transects), and used to analyze the effects of the Tupinambás Ecological Station and Abrolhos Marine National Park on fish assemblages. For this, fish assemblage characteristics, such as richness, abundance, biomass and body size, were compared to areas where fishing is allowed, and the habitat complexity was estimated through the footages. Concerning methods comparison, stereo-DOV showed to be more effective, sampling more richness and abundance within less effort, and Stereo-BRUVs showed to sample a very specific assemblage, comprised mostly by mobile and large bodied fish species, usually targeted by fisheries. Within both NTRs evaluated, target species characteristics was explained by protection status, while non-target species assemblage were more related to habitat characteristics. The results include an implementation of non-destructive ichthyofauna sampling techniques in Brazil, a generation of knowledge about fish ecology and the dissemination of the importance of these protected areas, which will assist management measures and encourage the preservation of the region.